2002
DOI: 10.1645/0022-3395(2002)088[0308:pisaso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Size and Shedding of Fasciola Hepatica Eggs by Naturally and Experimentally Infected Murid Rodents

Abstract: Using samples collected on the island of Corsica, a comparative study was done of the morphometry of Fasciola hepatica eggs shed by cattle and by naturally and experimentally infected murid rodents (wild Mus musculus and Rattus rattus and Rattus norvegicus Wistar laboratory strain). Eggs shed by murids are smaller in size than those shed by naturally infected cattle. A second study analyzed the number of F. hepatica eggs shed in murid feces at different time intervals, i.e., months, days, and 6-hr periods, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 9 publications
2
41
0
Order By: Relevance
“…A similar lack of total effectiveness has been reported in previous studies (Torgerson and Claxton 1999). In the present study, the residual presence of this parasite was probably due to contamination of the pasture by infected hares, which may act as competent reservoirs, as found for the nutria (Myocastor cypus) by Ménard et al (2001) in France and for the black rat (Rattus rattus) by Adela Valero et al (2002) in Corsica.…”
Section: Discussionsupporting
confidence: 53%
“…A similar lack of total effectiveness has been reported in previous studies (Torgerson and Claxton 1999). In the present study, the residual presence of this parasite was probably due to contamination of the pasture by infected hares, which may act as competent reservoirs, as found for the nutria (Myocastor cypus) by Ménard et al (2001) in France and for the black rat (Rattus rattus) by Adela Valero et al (2002) in Corsica.…”
Section: Discussionsupporting
confidence: 53%
“…For an accurate morphometric comparison, increases in the different biometric parameters which occur during digenean development within the definitive host according to growth laws (Dawes and Hughes 1964;Valero et al 1996Valero et al , 1998Valero et al , 2002 must be taken into account. If adult populations of different ages are studied, morphometric differences attributable to age can appear.…”
Section: Allometrymentioning
confidence: 99%
“…Their small size may account for the numerous constraints and adjustments reported for the digenean. Parasite eggs shed by murids are smaller than those shed by naturally infected cattle (Valero et al 2002). The biometric study of the parasite revealed that adult body size (at sexual maturity) is smaller in wild Corsican black rat than that in Bos taurus (Valero et al 1996).…”
Section: Fasciola Infection and Extreme Physiological Responsesmentioning
confidence: 99%
“…Although rats are only occasionally infected by the liver fluke on a worldwide basis (Li 1952; Molan and Hussein 1988), high prevalence has been reported in black rats (Rattus rattus) on the Mediterranean island of Corsica (Mas-Coma et al 1988). A series of studies demonstrated that the murid rodent may play an important role in the transmission of the disease on this island (Mas-Coma et al 1987, 1988Valero et al 1998Valero et al , 2002.…”
Section: Introductionmentioning
confidence: 99%